A Comet Assay for DNA Damage and Repair After Exposure to Carbon-Ion Beams or X-rays in Saccharomyces Cerevisiae. Issue 3 (9th August 2018) - Zhang, Miaomiao; Cao, Guozhen; Guo, Xiaopeng; Gao, Yue; Li, Wenjian; Lu, Dong
Ionizing radiation (IR) can result in serious genomic instability and genotoxicity by causing DNA damage. Carbon ion (CI) beams and X-rays are typical IRs and possess high-linear energy transfer (LET) and low-LET, respectively. In this article, a comet assay that was optimized by decreasing the electrophoresis time (8 minutes) and voltage (0.5 V/cm) was performed to elucidate and quantify the DNA damage induced by CI or X-rays radiation. Two quantitative methods for the comet assay, namely, comet score and olive tail moment, were compared, and the appropriate means and parameter values were selected for the present assay. The dose–effect relationship for CI or X-rays radiation and the DNA repair process were studied in yeast cells. These results showed that the quadratic function fitted the dose–effect relationship after CI or X-rays exposure, and the trend for the models fitted the dose–effect curves for various repair times was precisely described by the cubic function. A kinetics model was also creatively used to describe the process of DNA repair, and equations were calculated within repairable ranges that could be used to roughly evaluate the process and time necessary for DNA repair.